Gambaran Penerapan Respiratory Hygiene Di Masyarakat Kecamatan Baiturrahman Kota Banda Aceh Pada Masa Pandemi COVID-19 - Safarianti Safarianti; Zahratul Aini; Ayu Humaira (Majalah Kedokteran Indonesia, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is an infectious respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2). The Indonesian government and the World Health Organization (WHO) have made some efforts in the fight against the spread of COVID-19, one of which is by implementing respiratory hygiene. Respiratory hygiene, as an on-pharmaceutical intervention (NPIs), is one of the prevention measures designed to limit the transmission of respiratory infection spread by airborne and droplet routes. Method: This study used a descriptive research method with a simple random sampling technique. One hundred six people from ten villages in Baiturrahman Sub-district were selected as the subject of the study. The data were collected using an online questionnaire (google form). The obtained data were analyzed through univariate analysis. Result: The results revealed that only 4 respondents (3,8%) had a high level of respiratory hygiene compliance, 57 respondents (53,8%) were fairly compliant with respiratory hygiene, and 45 respondents (42,5%) had a very low respiratory hygiene compliance level. The study also found that 50% of respondents had used non-medical masks when doing activities outside the home, and 8.5% had applied physical distancing. Conclusion: The compliance level of good respiratory hygiene in the Baiturrahman Sub-District in Banda Aceh is still low, and the most common COVID-19 precautions the community takes are the use of non-medical masks when doing activities outside the home.